E-Community / Tan Samuel - Tan, Samuel (2003)
The WXES 3182 report first presents the background information on the project and the introductory presentation of E-Community system, as well as the system implementation, testing and evaluation of the system as a whole, which will comprise of these main modules; the Events and Happenings Module and the Discussion Forum Module will cater the project objectives of developing an online interaction space where people connect to one another for sharing of interests and ideas via the Internet. Methodologies and techniques, used in the researches on solving project limitation and problems and discussions on the systematic approach used in developing the project with emphasis on the chosen Waterfall process model was also written in brevity Having done the researched literature reviews which include researches and analysis on existing system , project d mains, tools, techniques and methodologic available in developing the E-Community project, I have decided to adopt the Microsoft.NET Framework, together with Visual Studio.NET, to develop my E-Community project in the development, coding and programming phases. A comprehensive analysis on the E-Community system was thoroughly carried out to understand the current problem and also, capturing the functional and nonfunctional requirements and the hardware/software requirements of the project, which was listed down in the report. In conclusion, much consideration have also been taken on the design of the proposed system, which includes integration of all modules into a system that has the functionalities as specified in requirements specification, the system design, user interface design of the module in the system, in ensuring a smooth system implementation, testing and evaluation towards accomplishing a bug-free, quality web application.